Papieski Wydział Teologiczny w Warszawie - Miazek, Jan; Kubacki, Zbigniew (Studia Nauk Teologicznych PAN, 2020)
Th e Pontifi cal Faculty of Th eology in Warsaw, the Bobolanum Section, off ers the graduate studies in theology for full-time and part-time students. It runs also a special program in spirituality. Bobolanum publishes two journals: “Studia Bobolanum” which appears 4 times a year and is dedicated to theological issues, and “Forum Iuridicum” - which appears once a year and is dedicated to law and canon law issues. In addition Bobolanum publishes the books of its professors in the series called “Seria Bobolanum”. Twice a year Boblanum organizes a symposium on a particular theme, for instance: “Children of Abraham: Th e Concept of God in Judaism, Islam and Christianity”. Th e section also proposes conferences opened to a larger public. Th e theme of the conferences in the academic year 2007/2008 was: “Spirituality of the Great Religions”. Th e main objectives of Bobolanum are to conduct research in theology and other religious fi elds as well as student education in those areas. Bobolanum desires to form students’ attitude in a spirit of human values, European heritage, good citizenship, patriotic and Christian values in the spirit of a dialogue with other Churches, religions, contemporary culture and science. While performing its tasks, Bobolanum is guided by the teaching of the Roman-Catholic Church and by the respect for individual and communal rights within the framework of a legal system. At the same time Bobolanum respects academic freedom necessary for eff ective and fair performance in the area of scientifi c research and education. Personal and institutional research programmes, symposiums and conferences, publications and information bulletins serve to fulfi l teaching and educational objectives. Bobolanum cooperates with various Polish and foreign academic centres. Lectures, classes, seminars, individual internships and other activities carried by teachers and students together serve to fulfi l didactical and educational tasks. Students of the fi rst two years attend an intensive English language course that gives them the language competence at B2 level.